Answer:
The vertex form of the given equation is f(x) = (x+7/2)²+(-61/4) where vertex is (-7/2,-61/4).
Explanation:
We have given a quadratic equation in standard form.
f (x)= x²+7x-3
We have to rewrite given equation in vertex form.
y = a(x-h)²+k is vertex form of equation where (h,k) is vertex of equation.
We will use method of completing square to solve this.
Adding and subtracting (7/2)² to above equation, we have
f(x) = x²+7x-3+(7/2)²-(7/2)²
f(x) = x²+7x+(7/2)²-3-(7/2)²
f(x) = (x+7/2)²-3-49/4
f(x) = (x+7/2)²+(-12-49)/4
f(x) = (x+7/2)²+(-61/4)
Hence, The vertex form of the given equation is f(x) = (x+7/2)²+(-61/4) where vertex is (-7/2,-61/4).